Pendekatan Community Based Disaster Management (CBDM) Melalui Kampung Siaga Bencana (KSB) di Kelurahan Jatibening - Laveda, Anggita Talita; Ningsih, Sari; Setyawati, Kiki (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2024)
This research discusses community-based disaster management efforts in Indonesia, especially through the Disaster Alert Village program in Jatibening Baru Village, Bekasi City. Aims to analyze the implementation of Community Based Disaster Management (CBDM) in the Disaster Preparedness Village program with a focus on disaster mitigation, priority handling, evaluation of disaster management performance, and resource mobilization. The research method used is a descriptive qualitative method and refers to the theory of Community-Based Disaster Management. The research results found that the research results show that disaster management involves three important stages, namely before, during and after a disaster occurs. The aim of this series of activities is to reduce disaster risks and increase community resilience in facing them. The active role of government and community participation is very important in efforts to better manage disaster risks. There are several supporting factors for Community Based Disaster Management (CBDM) in Disaster Preparedness Villages (KSB), namely: (1) Availability of an adequate budget is very important in implementing the KSB program (2) Citizen participation (3) Establishment of good communication between all stakeholders. Meanwhile, the inhibiting factors for Community Based Disaster Management (CBDM) in Disaster Preparedness Villages (KSB) are: (1) Socialization and training that are not yet optimal; (2) Lack of logistics storage warehouses (3) Lack of enforcement of DAS (River Watershed) regulations